Analysis of the combined effect of long-term heat light soaking and KF/NaF post-deposition treatment on the open-circuit voltage loss in CIGS solar cells. (1st May 2022) - Tangara, Hamidou; He, Yulu; Islam, Muhammad Monirul; Ishizuka, Shogo; Sakurai, Takeaki
Abstract: Heat light soaking (HLS) has been known to impact the photovoltaic parameters of Cu(In, Ga)Se2 (CIGS) solar cells for a long time. Recently, the focus shifted to the effect of the procedure on alkali fluoride-treated CIGS. Here, we investigate the impact of long-term HLS on the open-circuit ( V OC ) loss in high-efficiency CIGS with potassium fluoride (KF) and sodium fluoride (NaF) post-deposition treatment (PDT). HLS is shown to increase the net doping density, however, the subsequent improvement of the V OC is lower than expected. Using an analysis based on the SQ theory, we show that HLS reduces the nonradiative recombination rate in the bulk but increases the one at the interface. We present a model to explain the increase of interface recombination. We further demonstrate that a combination of HLS and KF/NaF-PDT is necessary to enhance the positive impacts of HLS and mitigate the detrimental ones leading to high-efficiency CIGS devices (22%).